La formazione della Democrazia Cristiana a Napoli (agosto 1943 - gennaio 1944) The Formation of the Christian Democracy Party in Naples (august 1943 - january 1944) - Roberto P. Violi (Clio: Saggi di scienze storiche, archeologiche e storico-artistiche, 2004)
In this book, the dynamics of a nascent political organization in relation to the question of powers and institutions of the Southern Kingdom during the years of 1943-44 are analyzed. The Southern party of DC, taking advantage of both old and new forms of politics, would soon benefit, in addition to the experience of Luigi Sturzo's populism, of an emerging political class and of the increased weight of the Church in the material and civil crisis caused by the war. In Naples, one of the foremost political headquarters of the liberated Italy, the Catholic Party faced the difficulty of an unconditional membership carried out by the ecclesiastical hierarchy and large sections of the populace to traditional monarchical authority, while its leading group acted from the inside in the context of the pluralistic political and democracy system going out in Cln.